Ultra-low power design strategy for two-stage amplifier topologies - Leene,LB; Constandinou,TG (Electronics Letters, 2014)
A novel two-stage amplifier topology and ultra-low power design strategy for two-stage amplifiers that utilises pole zero cancellation to address the additional power requirements for stability are presented. For a 288 nA total bias, the presented amplifier achieves a 1.07 MHz unity gain frequency with a 8560 pF MHz/mA figure of merit.